Impact of human body shape on free convection heat transfer - Shri H. Viswanathan; Ankit Joshi; Lyle Bartels; Kambiz Sadeghi; Jennifer K. Vanos; Konrad Rykaczewski (PLoS ONE, 2025)
Understanding the thermal comfort and safety of diverse populations within indoor settings requires a quantitative understanding of the primary heat exchange pathways between occupants and their surroundings: radiation and free convection. Thus far, however, free convective heat transfer coefficients have only been determined for the average Western adult. To this end, we investigated how variation in body shape impacts free convection heat transfer using an experimentally validated numerical model. The multiphysics model was compared against experiments conducted using the thermal manikin ANDI ("Advanced Newton Dynamic Instrument") in a climate-controlled enclosure across five air-to-skin temperature differences ranging from 4.9 to 13.9°C. The difference between measured and simulated heat fluxes for the whole body, and per anatomical region, was typically <5%, occasionally reaching 15–20%, for some body regions due to physical features not modeled in the virtual ANDI model. Using the validated model, we simulated free convection around a family, or diverse group, of virtual manikins representing the 1st to 99th percentile body mass index (BMI) and height variation in the United States adult population. Our results show that the free convection heat transfer coefficient is independent of human sex and height but decreases slightly with increased BMI. However, the variation from the average manikin in the whole body and regional free convection coefficients with BMI was small, not exceeding 8% and 16%, respectively. Furthermore, our regression coefficients and exponents can be derived from the theorical correlation for free turbulent convection from a vertical plate, which also explains the observed independence of the heat transfer coefficient from the manikins’ height. Overall, these findings demonstrate the general applicability of using an average body shape in indoor thermal audits and/or overheating risk assessments to understand thermal comfort and heat stress. The results and valid application of the model support critical insights for human health, productivity, and well-being connected to heat and cooling in buildings.